Modern Approach to Formation of the Banking Sector Development Trajectory - Diatlova, Yu. (Економічний вісник Донбасу, 2020)
The results of the study topical issue on effective development of the banking sector with an emphasis on banks with domestic capital are summarized in the article; the modern approach to formatting the trajectory of such development is substantiated. The factors influencing the development of the banking sector are systematized. External and internal factors are distinguished. The supranational and national levels are defined for the group of external factors. Supranational factors are related to globalization and integration. First of all, these are crisis phenomena in the world economy and financial system, the liberalization of capital movements. External factors at the national level mostly have a negative impact on the development of the banking sector. It is shown that certain external factors of the national level depend on supranational ones, and internal factors depend on national ones. Internal factors are grouped into those that have a positive and negative impact on the development of the banking sector. The characteristic of the most significant factors is given, their mutual influence is shown. Factors such as the dangerous level of competitive internalization due to the presence of foreign banks in the Ukrainian banking market, the high level of loans and deposits dollarization, low quality of assets and loans have a negative impact on the development of the banking sector. The influence of internal factors on the development of the banking sector is determined. It is proved using dynamic (simulation) modeling based on an impulse process that the development of the banking sector is significantly influenced by the factor of dangerous level of competitive internalization. It is established that such stabilizing factors as the growth of demand for banking services, increasing confidence in the banking system and stabilization of the national currency together compensate for the destabilizing effect of any negative factor, including competitive internalization. The formation of positive internal factors will contribute to the progressive trajectory of the banking sector development, in particular banks with domestic capital.